Performance Analysis of Intel Core i7-10610U and Intel Core i7-1265U CPUs Using Benchmarking Method: Analisis Performa CPU Intel Core i7-10610U dan Intel Core i7-1265U Menggunakan Metode Benchmarking - Hastomo, Mursid Dwi; Presdianto, Eko; Riwurohi, Jan Everhard (RADIANT: Journal of Applied, Social, and Education Studies, 2025)
Since its introduction, technology that utilizes semiconductor chips to perform data processing and computing or commonly known as microprocessors has experienced various advances and improvements in every aspect. Various innovations have been produced by microprocessor manufacturing companies, namely Intel, to adjust the Central Processing Unit (CPU) to its function. Intel periodically recreates microprocessors that have previously been on the market. The purpose of this study is to determine how significant the difference in performance is between one generation and the next. The launch of CPU products with the same type, but from different generations, shows that each CPU launched at different times always has an increase in performance compared to its predecessor. So, what causes this increase in performance? This question will be answered through testing between the Intel Core i7-10610U and Intel Core i7-1265U Passmark software version. 11. 1 and CPU-Z version. 15. 0. The use of several test tools aims to ensure that the benchmarking results are not biased from only one source and provide a comprehensive picture of the performance of each processor. The benchmarking method is the main measuring tool, while performance comparison is the purpose of the analysis. The tests performed include integer math, compression, floating point math, extended instructions/Streaming SIMD Extensions (SSE), encryption, sorting, Frequency, Single-Thread and Multi-Thread. The results of this test show that the Intel Core i7-1265U has superior performance to the Intel Core i7-10610U. This is because the number of cores, threads, and bandwidth owned by the Intel Core i7-1265U is larger and more, namely 12 threads and 54.1 GB/s for bandwidth, while the Intel Core i7-10610U has 8 threads and 45.8 GB/s bandwidth.